(untitled) (The Journal of Psychology and Sociology, 2012)
In the article the authors observe formation of emotional intelligence at preschool age in child development process. Information on features of formation of emotional intelligence and what kind of factors inﬂ uence on its formation is given in general. Emotional life of the child stands aside, in spite of the fact that for development of child knowledge it is devoted much time.